THE REINFORCEMENT OF THE CHARACTER VALUES IN THE HISTORY SUBJECT AT SMA NEGERI 1 KOTA YOGYAKARTA - Titan Rohkmutiana Hardhi; Ajat Sudrajat (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
ABSTRACTThis research aimed to identify and describe the way reinforce of the character values were being taught in the history subject at SMA Negeri 1 Kota Yogyakarta. This research was a naturalistic qualitative research. The data were collected through observation, interviews, and documentation. The data trustworthinnes was enhanced by source triangulation. The techniques used to analyse the data were the Miles and Hubberman model which consisted of data reduction, data display, and data verification. The result of the research showed that were three methods were used in the reinforcement of the character values i.e. leading by examples, habituation, and mechanism of the appreciation and sanctions. (a) Leading by examples were earned on teachers and advice of history itself;  (b) habituation was done by conditioning the students while doing tasks and  discussions; and (c) the mechanism of appreciation and sanction is contained in the learning contract, aiming for students to be motivated and maximize reinforcement. Meanwhile reinforcement that done in learning should be positive reinforcement. Keyword: history subject, character values, reinforcement of the character values.